2021
DOI: 10.1136/bmjsem-2020-000960
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity and sedentary behaviours from before to during the COVID-19 pandemic lockdown: a systematic review

Abstract: ObjectiveIn March 2020, several countries banned unnecessary outdoor activities during COVID-19, commonly called ‘lockdowns. These lockdowns have the potential to impact associated levels of physical activity and sedentary behaviour. Given the numerous health outcomes associated with physical activity and sedentary behaviour, the aim of this review was to summarise literature that investigated differences in physical activity and sedentary behaviour before vs during the COVID-19 lockdown.Design, data sources a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

84
909
9
45

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 977 publications
(1,047 citation statements)
references
References 103 publications
84
909
9
45
Order By: Relevance
“…Despite efforts to keep people physically active during social isolation [30], the implemented strategies do not appear to have been effective in increasing PA and reducing ST [31]. This situation has an immediate impact on people's health because of the negative effect on the immune system and, thus, a greater predisposition to contagion [32].…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to keep people physically active during social isolation [30], the implemented strategies do not appear to have been effective in increasing PA and reducing ST [31]. This situation has an immediate impact on people's health because of the negative effect on the immune system and, thus, a greater predisposition to contagion [32].…”
Section: Discussionmentioning
confidence: 99%
“…An inadvertent consequence of COVID public health protocols has been a decline in physical activity. A systematic review of 66 studies examining physical activity and sedentary behavior during COVID demonstrated consistent declines in physical activity during the initial COVID-19 lockdown regardless of subpopulation or methodology used (21). Such observations are not unexpected given widespread closure of recreation facilities and public parks, a shift to working from home, and shelter-in-place protocols.…”
Section: Physical Activity In the Time Of Covid-19mentioning
confidence: 91%
“…15 Further, early evidence suggest such populations are more likely suffer the most during and after the pandemic. 4, 1620 Research conducted during COVID-19 has already reported low levels and significant reductions of children’s PA. 21, 22 It is essential to understand the impact of the pandemic on PA levels and behaviours for different ethnic groups for two reasons, first to prevent inactive behaviours becoming entrenched and second, to tailor support for different populations by addressing the root causes of PA inequality within different populations. 23…”
Section: Introductionmentioning
confidence: 99%